جريمة إفشاء السر المهني - الشعراني فادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يرتبط السر غالباً بحق الانسان في ضمان حريته الشخصية التي كفلتها الدساتير والتشريعات الوطنية والدولية ومؤدى ذلك أن افشاء السر يسيء إلى مكانة صاحبه ويمس شرفه واعتباره وهذا ما يفسر لنا الحاق الشارع هذه الجريمة بالجرائم الماسة بالشرف والاعتبار. فالحكمة من تجريم افشاء الاسرار هي المحافظة على السر المهني الذي بدأ واجباً أخلاقياً تقتضيه مبادئ الشرف والأمانة ومن ثم التزاماً قانونياً لحماية صاحب السر ومكانته الاجتماعية من جهة وصيانة المصلحة العامة في المجتمع في عدم تعريض سمعة المهن النبيلة للإهانة وعدم الثقة بها من جهة أخرى كالطب والقضاء وغيرها من المهن الاضطرارية فإن لم يجد المريض الطبيب الذي يودع إليه سره أو لم يجد المتهم محام يصارحه بسره لأدى ذلك إلى المساس بحرية وحقوق الانسان والاضرار بالمجتمع . لذلك فإن البحث في موضوع السر المهني يتطلب بيان مفهومه والاساس القانوني في الالتزام به وعناصر تجريمه وحالات الخروج عن قاعدة الحفاظ على السر المهني خاصةً في ضوء الغموض الذي اعتراه في تشريعنا السوري باستثناء وجود بعض التشريعات الخاصة التي جاءت بأحكام ناظمة لكل مهنة على حدى . The secret is linked to the right of the person to guarantee his personal freedom guaranteed by national and international constitutions and legislations, and the result is that disclosure of the secret harms the position of the owner and touches his honor and consideration. This is what informs us that the legislator committed this crime with crimes of honor and consideration. The wisdom of criminalizing the disclosure of the secret is to preserve the secret of the profession, which began a moral duty ,which is related to the principles of honor and honesty and then a legal obligation to protect the owner of the secret and social status on the one hand and maintenance of the public interest in society not to expose the reputation of noble professions to insult and distrust them, of the forced professions, if the patient does not find the doctor who filed a secret or did not find the accused lawyer to arbitrate him in secret to lead to prejudice to freedom and human rights and damage to society. Therefore, research on the subject of professional confidentiality requires a statement of its concept, the legal basis of its commitment and the elements of its criminalization and cases of departing from the rule of maintaining the secret of the profession, especially in the light of the ambiguity in the Syrian legislation, except for the existence of some legislations that govern the provisions of each profession.